THE POETRY WORKSHOP MINISTRY OF CULTURE IN NICARAGUA IN THE EIGHTY YEARS - Pastrana Hernández, Guadalupe Xochitlanetzin (Humanismo y Cambio Social, 2015)
The victory of Sandinista Revolution involved deep transformation to Nicaragua in several fields, one of them Culture. With the creation of the Ministry of Culture, whose Minister was Ernesto Cardenal, - where carried out among other projects- Poetry Popular Workshops, Show the history of this workshops, its ways of organization, poets that were involved, that still writing. Also mention about the controversy between Nicaraguan intellectuals, due to some of them thought that workshops limited poetry creation, is one of the aims of this essay. As well aims make a contribution to understand and read into from other perspectives the new Nicaragua that at the end of 80´s decade (when Mexico and other Latin American countries was told of neoliberalism) was an example of dignity an rebellion. Keywords: nicaraguan poetry, popular poetry, workshop poetry.